2021
DOI: 10.3390/foods10123085
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Effects of Inonotus obliquus Polysaccharide In Vivo and In Vitro

Abstract: Excessive lipid intake will cause hyperlipidemia, fatty liver metabolism disease, and endanger people’s health. Edible fungus polysaccharide is a natural active substance for lipid lowering. In this study, the HepG2 cell model induced by oleic acid and mice model induced by a high-fat diet was established. The lipid-lowering effects of Inonotus obliquus polysaccharide (IOP) was investigated in vivo and in vitro. Glucose (251.33 mg/g), rhamnose (11.53 mg/g), ribose (5.10 mg/g), glucuronic acid (6.30 mg/g), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Known polysaccharides with bile acid binding activity were also isolated from Abelmoschus esculentus [ 62 ], Kadsura coccinea [ 63 ], and Laminaria japonica [ 64 ], and in all cases, the presence of uronic acids was determined as a basic principle for effect manifestation [ 65 ]. The lipid lowering effect of Inonotus obliquus and Volvariella volvacea polysaccharides was associated with their fat and cholesterol binding [ 66 , 67 ], providing the hypolipidemic activity of polymers. In addition, the pancreatic lipase inhibition plays an important role in the lipid lowering effect of plant food and polysaccharide-derived products.…”
Section: Resultsmentioning
confidence: 99%
“…Known polysaccharides with bile acid binding activity were also isolated from Abelmoschus esculentus [ 62 ], Kadsura coccinea [ 63 ], and Laminaria japonica [ 64 ], and in all cases, the presence of uronic acids was determined as a basic principle for effect manifestation [ 65 ]. The lipid lowering effect of Inonotus obliquus and Volvariella volvacea polysaccharides was associated with their fat and cholesterol binding [ 66 , 67 ], providing the hypolipidemic activity of polymers. In addition, the pancreatic lipase inhibition plays an important role in the lipid lowering effect of plant food and polysaccharide-derived products.…”
Section: Resultsmentioning
confidence: 99%
“…DNA sequencing of caecal microbiota revealed that the ameliorative effects of IOP on obesity are through modification of the microbiota metabolism, particularly an increase in butyrate-production-associated bacteria Lactobacillus and Bacteroidales S24-7, as well as short-chain fatty acid-producing bacteria Holdemanella and Ruminococcaceae_UCG-014 (Yu et al 2020 ). Furthermore, IOP can significantly reduce serum total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) contents, while increasing high-density lipoprotein-cholesterol (HDL-C) content both in vitro in oleic acid-induced HepG2 cells and in vivo in mice fed with a high-fat diet (Yang et al 2021 ; Lin et al 2023 ). A successful decrease in the weight gain of mice induced by a high-fat diet was also observed after 10 weeks of IOP treatment (Yang et al 2021 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
“…Furthermore, IOP can significantly reduce serum total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) contents, while increasing high-density lipoprotein-cholesterol (HDL-C) content both in vitro in oleic acid-induced HepG2 cells and in vivo in mice fed with a high-fat diet (Yang et al 2021 ; Lin et al 2023 ). A successful decrease in the weight gain of mice induced by a high-fat diet was also observed after 10 weeks of IOP treatment (Yang et al 2021 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
“…On the one hand, it is of substantial consequence to delve into the underlying mechanism of its biological activity. On the other hand, previous studies lacked reproducibility, so it is of great significance for us to further study the lipid‐lowering active components of IOP and its mechanism (Xu et al., 2019 ; Yang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%